Tying up the Ends: Plasticity in the Recognition of ssDNA at Telomeres - Lloyd, Neil R. (Biochemistry, 2016)
Telomeres terminate nearly exclusively in ssDNA overhangs comprised of the G-rich 3′ end. This overhang varies widely in length from species to species, ranging from just a few bases to several hundred nucleotides. These overhangs are not merely a remnant of DNA replication, but rather are the result of complex further processing. Proper management of the telomeric overhang is required both to deter the action of the DNA-damage machinery and to present the ends properly to the replicative enzyme telomerase. This Current Topic review addresses the biochemical and structural features used by the proteins that manage these variable telomeric overhangs. The Pot1 protein tightly binds the single-stranded overhang, preventing DNA damage sensors from binding. Pot1 also orchestrates the access of telomerase to that same substrate. The remarkable plasticity of the binding interface exhibited by the S. pombe Pot1 provides mechanistic insight into how these roles may be accomplished, and disease-associated mutations clustered around the DNA-binding interface in the hPOT1 highlight the importance of this function. The budding yeast Cdc13-Stn1-Ten1, a telomeric RPA complex closely associated with telomere function, also interacts with ssDNA in a fashion that allows degenerate sequences to be recognized. A related human complex composed of hCTC1-hSTN1-hTEN1 has recently emerged with links to both telomere maintenance and general DNA replication and also exhibits mutations associated with telomere pathologies. Overall, these sequence-specific ssDNA binders exhibit a range of recognition properties that allow them to perform their unique biological functions.